How does spinopelvic mobility and sagittal functional cup orientation affect patient-reported outcome 1 year after THA?: a prospective diagnostic cohort study - Innmann, Moritz Maximilian; Reichel, Franz; Merle, Christian (The journal of arthroplasty, 2021)
Background - This prospective cohort study aimed to characterize how spinopelvic characteristics change post-total hip arthroplasty (THA) and determine how patient-reported outcome measures are associated with 1) individual spinopelvic mobility and 2) functional sagittal cup orientation post-THA. - Methods - One hundred consecutive patients who received unilateral THAs for end-stage hip osteoarthritis, without spinal pathology were studied. Preoperatively and postoperatively, patients underwent clinical and radiographic evaluations. Patient-reported outcomes were collected using the hip disability and osteoarthritis outcome score - physical function shortform (HOOS-PS). Radiographic parameters measured from standing and relaxed-seated radiographs, included the lumbar lordosis angle, pelvic tilt, pelvic femoral angle and cup orientation in the coronal (inclination/anteversion) and sagittal (anteinclination) planes. Spinopelvic mobility was characterized (ΔPT: “stiff” [<10°], “normal” [10°-30°], and “hypermobile” [>30°]). - Results - Preoperative spinopelvic characteristics were not associated with HOOS-PS. Post-THA, the spinopelvic characteristics changed, with less patients having spinopelvic hypermobility (7%) compared with preop (14%). Postoperatively, patients with spinopelvic hypermobility showed significantly worse HOOS-PS scores (21 ± 17 vs 21 ± 22 vs 41 ± 23; ANOVA P = .037). Sagittal but not coronal cup orientation was associated with postoperative spinopelvic characteristics. Cup anteinclination was less in the patients with postoperative spinopelvic hypermobility (27 ± 7° vs 36 ± 8° vs 36 ± 10°; ANOVA: P = .035). - Conclusion - We hypothesize that spinopelvic hypermobility is secondary to impingement and reduced hip flexion; to achieve a seated position, impinging hips require more posterior pelvic tilt. Patients with spinopelvic hypermobility are likely impinging secondary to the low cup anteinclination (sagittal malorientation despite optimum coronal orientation) and thus have lower HOOS-PS compared. Sagittal assessments are thus important to adequately study hip mechanics. - Level of Evidence - Level II, diagnostic study.